EFEK MODERASI BUDAYA ORGANISASI PADA PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA PEGAWAI - Rahadhini, Marjam Desma (Universitas Slamet Riyadi, 2010)
ABSTRACT The objective of this research is to analyze (1) the influence of organizational culture moderate transformational leadership on employee performance, (2) the organizational culture of moderation effect in strengthening the influence of transformational leadership on employee performance. This research locations in Education Department of Sukoharjo. Sample of this research uses 48 employees taken to the purposive sampling technique. Scope of research focuses on aspects of transformational leadership and its impact on employee performance with organizational culture as moderating. Based on the analysis of obtained results indicate that transformational leadership variables have a significant effect on employee performance. This is evidenced by the p value 0,024 < 0,05. Organizational culture variables have a significant effect on employee performance. This is evidenced by the p value 0,019 < 0,05. Interaction variables have a significant effect on employee performance. This is evidenced by the p value 0,014 < 0,05. The findings of this research indicate that organizational culture moderate the influence of transformational leadership on employee performance in Education Department of Sukoharjo. Based on first regression analysis obtained the value of Adjusted R2 = 0,149. This Adjusted R2 in second regression increased to 0,243. From the regression analysis comparison of an increase in Adjusted R2 of 0,094. This shows that the organizational culture strengthen the influence of transformational leadership on employee performance. Keywords: transformational leadership, organization culture, and the employee’s performance